Process of infection with bacteriophage phiX174. XXXVII. RNA metabolism in phiX174-infected cells. - Clements, J B (1975)
The RNA produced in vivo from bacteriophage phiX174 DNA has been analyzed by polyacrylamide-agarose gel electrophoresis and sedimentation in dimethyl sulfoxide gradients, and the results of Hayashi and Hayashi (1970) have been confirmed and extended. An efficient procedure for recovery of RNA from gels, followed by a hybridization assay, has indicated the presence in infected cells of 18 distinct RNA species with sizes up to and greater than the unit (viral) length. The sizes of phiX mRNA's were similar irrespective of whether material was analyzed on gels or in dimethyl sulfoxide gradients. When virus-induced RNA was detected by a double-label method, seven additional low-molecular weight species were observed on gels and the resolution of dimethyl sulfoxide gradients was enhanced. The present results lend support to aspects of the model of Hayashi and Hayashi (1970) for the generation of these discrete mRNA species; an alternative model is also discussed.